Thidiazuron-induced morphogenesis in tamarind seedlings - Mehta, Urmil J.; Sahasrabudhe, N.; Hazra, Sulekha (In Vitro Cellular & Developmental Biology-Plant, 2005)
Germination of tamarind seeds in medium containing thidiazuron (TDZ) resulted in induction of nodular protrusions in and around the cotyledonary node meristem. The structures developed radially in well-defined circles and subsequently spread towards the cotyledonary bridge and also in the proximal part of the hypocotyl. The structures developed into shoots on transfer to medium devoid of growth regulators. Histological studies revealed that the protrusions initiated from the nodal meristem and extended to the non-meristematic region between the two meristems and also in the proximal part of the hypocotyl in seedlings germinated in 9.08 mu M TDZ. Newly formed cell layers and less-differentiated meristematic protrusions were also seen. With the increase in the distance from the meristem, the buds were less differentiated; in the proximal part of the hypocotyl only the multiple layers of meristematic cells were noted. With extension of the period of incubation, the TDZ-induced meristematic activity extended laterally in circles towards the neighboring region. The radial spread of the meristematic activity from the center of the nodal meristem was also evident at 18.16 mu M TDZ. From the pattern of the morphogenic development and the histological studies it may be hypothesized that in tamarind, TDZ influences the existing meristems specifically. Subsequently de novo organogenesis is triggered in the neighboring cells.
Keywords: Caulogenesis; Histology; morphogenesis; protrusions; thidiazuron

Graphene nanosheets assisted carbon hollow cylinder for high-performance field emission applications - Tripathi, Prashant; Gupta, Bipin Kumar; Bankar, Prashant K.; More, Mahendra A.; Late, Dattatray J.; Srivastava, Onkar Nath (Materials Research Express, 2019)
Electron sources are critical constituents for myriad many electronic applications including electron imaging, mass spectroscopy etc. Here, we report the realization of high-performance field emission from graphene assisted carbon hollow cylinders (Gr-CHCs) composed of multi-stacked radially aligned CNTs. These CHCs have built-in synthesis related Fe nanoparticles (NPs). This engineered nano-structure exhibits excellent field emission properties such as one of the ultra-low turn-on field (0.64V mu m(-1) at 10 mu A cm(-2)), low threshold field (0.74V mu m(-1) at 100 mu A cm(-2)), very high current density (15.49 mA cm(-2) at 1.32V mu m(-1)) which is nearly double the current density obtained in our previous study. High field enhancement factor (0.72. x. 10(4)) with highly stable emission current at 100 mu A was observed for more than 3 hrs at the base pressure of similar to 1. x. 10(-8) mbar. This study suggests an approach to enhance the current density using the proposed innovative nanostructure and forms the basic theme of this communication. Highly efficient and stable field emissions observed are attributed to the geometry of cylinder and the production of the high density of sharp protrusions within the graphene sheets which enhance the local electric field and dramatically enhance field emission. This innovative cylindrical geometry associated with graphene assisted on Fe bearing aligned CNTs along with the periphery of the bulk cylinder provides an easy injection of electrons from the conduction band of CHCs into the vacuum in the presence of an external electric field. The tunability of field emission properties of these CHCs can be easily achieved by tailoring their diameter (10 and 20 mm) and different concentrations of the precursor. This new approach of the graphene assisted cylindrical geometry-based field emitter source provides enormous prospects and demand for next-generation high resolutions display devices.
Keywords: Carbon nanotubes; field emission; graphene assisted carbon hollow cylinder; protrusions